PANC-3 score in predicting the severity of acute pancreatitis - Anandaravi BN,; Manjunath RD,; Shetty, Darshan (Asian Journal of Medical Sciences, 2022)
Background: Acute pancreatitis (AP) presents as acute abdomen, Inflammatory process of pancreas associated with local and systemic complications. Many scores (such as Ranson’s, APACHE II, and Bedside index for severity in AP) that help us in predicting severity at the time of admission, but these are time consuming and require complex calculation and are not economically cheap. Our aim here is to analyze the simplified stratification system of PANC3 SCORE and its assessment in predicting severity of AP as decided by Modified Marshall Score. Aims and Objectives: PANC-3 score in predicting the severity of acute pancreatitis. Materials and Methods: PANC3 Scoring system is simple, easy to access readily available and economic, as it involves these criteria (hematocrit, body mass index, and pleural effusion). It is a prospective study in which 100 patients were evaluated with PANC3 Scoring, who were diagnosed with AP and admitted to the department of general surgery, Mysore Medical College and Research Institute. Results: The results showed that PANC3 score had a 96.25% specificity, 70% sensitivity, 82.35% positive predictive value, and 92.77% negative predictive value. Conclusion: PANC3 SCORE is cost effective, can be determined at the time of admission, thus early prediction of disease severity and early referral to higher center.